Influence of synthesis parameters on the optical properties of carbon dots - Ángela J. García-Salcedo; Luz Ángela Giraldo-Pinto; Deibys Josué Márquez-Castro; Liliana Tirado-Mejía (Carbon Trends)
Photoluminescent carbon dots were synthesized by hydrothermal treatment from agricultural waste. Considering that the composition of the dots’ surface depends on the precursor source and that this composition influences the optical properties, this study focused on analyzing the effect of synthesis parameters on the formation of functional groups, on the core structure, on the morphology, and their influence on the absorption, excitation, emission, and quantum performance properties. It was obtained that by increasing the synthesis temperature, functional groups C = O, C = N, and CO were formed in the carbon dots obtained from the three precursors, and an additional group C = C in dots obtained from plantain peels, which are the only one that showed a degradation of the cellulose band. The absorption response indicated the formation of graphitic nuclei with oxygenated groups responsible for the red shift of the absorption maximum moving from 266 to 283 nm. The Raman response indicates that there are graphitic domains in the nucleus, where the defects band has a high intensity for the three precursors. The higher quantum yield value presented by the plantain dots is due to the surface, not the graphitic core. The spherical shape and size of around 2 nm were observed by TEM.